Myocardial dysfunction in treated adult hypopituitarism: a possible explanation for increased cardiovascular mortality. Issue 1 (January 1992) - Shahi, M; Beshyah, S A; Hackett, D; Sharp, P S; Johnston, D G; Foale, R A
Abstract : OBJECTIVE--To assess cardiac structure and function in patients with treated hypopituitarism and to determine their relation to the degree of growth hormone deficiency and body composition pattern. DESIGN--26 patients with treated hypopituitarism were studied by cross sectional and Doppler echocardiography and by exercise testing. The results were analysed and their relation to the degree of growth hormone deficiency and body composition determined. SETTING--All tests were performed in the department of cardiology and the unit of metabolic medicine at a tertiary referral centre. PATIENTS--Patients with hypopituitarism referred for endocrine assessment. MAIN OUTCOME MEASURES--Left ventricular mass, left ventricular diastolic function, and exercise capacity in patients with hypopituitarism and their relation to growth hormone deficiency. RESULTS--Mean (SD) serum concentration of insulin-like growth factor 1 (IGE-1), a measure of growth hormone deficiency, was 82.4 (45) micrograms/l. Lean body mass calculated by measuring total body potassium was 50 (9) kg. All patients had a normal left ventricular mass index and a normal left ventricular ejection fraction. Eight patients had abnormal left ventricular diastolic function. There was a significant correlation between IGF-1 and left ventricular mass (r = 0.45, p less than 0.02). Lean body mass was also significantly correlated with left ventricular mass (r = 0.78, p less than 0.0001) and left ventricular diastolic function (r = -0.63, p less than 0.01). The mean exercise duration was 8.6 (3.6) minutes. There was a significant correlation between serum IGF-1 and the rate-pressure product on exercise (r = 0.47, p less than 0.01). Seven patients had planar ST segment depression greater than 0.1 mV during exercise testing. In five of these patients there was rapid resolution of ST segment depression immediately after exercise. Two patients developed considerable ST segment depression, and subsequent coronary angiography showed normal coronary arteries. Exercise-induced ST segment depression was not related to the severity or duration of growth hormone deficiency or serum cholesterol concentration. CONCLUSIONS--This study suggests that left ventricular mass and the rate-pressure product are related to the degree of growth hormone deficiency, that left ventricular diastolic dysfunction is frequently seen in hypopituitarism, and that these patients may have ischaemic-like ST segment changes during exercise testing. These findings may explain the increased cardiovascular mortality in patients with hypopituitarism and may also have implications for growth hormone replacement therapy in adults.